2019
DOI: 10.9741/2578-2118.1055
|View full text |Cite
|
Sign up to set email alerts
|

Problems Faced by Secondary Technology Education Novice and Veteran Teachers

Abstract: The purpose of this study was to examine the challenges faced by secondary technology education (TE) teachers in Illinois. Specifically, the study sought to identify and categorize a list of challenges encountered during their first years in the TE profession as well as challenges that veteran TE teachers are facing in their current teaching assignment. Seventy-three TE teachers completed an online questionnaire. Twenty-six challenges were identified and of the top five challenges, only three, equipment, fundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This situation is not an exception for the new administrators. Several studies (Beam, Claxton & Smith, 2016;Arnett-Hartwick & Cannon, 2019) have revealed that novice administrators experience similar challenges in their roles. These challenges are various and discomforting for the new administrators.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is not an exception for the new administrators. Several studies (Beam, Claxton & Smith, 2016;Arnett-Hartwick & Cannon, 2019) have revealed that novice administrators experience similar challenges in their roles. These challenges are various and discomforting for the new administrators.…”
Section: Introductionmentioning
confidence: 99%